A system of equations and its solution are given below. System A Complete the sentences to explain what steps were followed to obtain the system of equations below. System B To get system B, the equation in system A was replaced by the sum of that equation and times the equation. The solution to system B the same as the solution to system A.

Respuesta :

Answer:

To get to system B the second equation in system A was replaced by the sum of that equation and the first equation multiplied by 4. The solution to system B is the same as the solution to system A.

Step-by-step explanation:

A system of equations and it’s solution are given below.

System A.

x-y=3

-2x+4y=-2

Solution: (5,2)

Complete the sentences to explain what steps were followed to option the system of equations below.

System B

x-y=3

2x=10

To get to system B the (first/second) equation in system A was replaced by the sum of that equation and the (first/second) equation multiplied by (4....2.....-3) . The solution to system B (is/ is not) the same as the solution to system A.

Solution:

To get system B:

First write the first equation in system A. x - y = 3

Multiply the second equation in system A by 4 and add to the first equation in system A to get:

2x = 10

x = 10/2 = 5

Put x = 5 in x - y = 3

5 - y = 3

y = 5 - 3 =2

The solution to system B is the sam as that of system A

To get to system B the second equation in system A was replaced by the sum of that equation and the first equation multiplied by 4. The solution to system B is the same as the solution to system A.

Answer:

The person above is correct

Step-by-step explanation: